Population-based strategies for Helicobacter pylori-associated disease management: a Japanese perspective - Shiota, Seiji (2010)
The prevalence of Helicobacter pylori infection is decreasing gradually in Japan mainly owing to an improvement in sanitary conditions. The guidelines for H. pylori management by the Japanese Society for Helicobacter Research, initially established in 2000 and revised in 2003, were revised dramatically in January 2009. The new guidelines accepted the use of new drugs and recommended trying the second-line eradication regimen. Moreover, the revised guidelines reflected the recent knowledge in Japan that metachronous gastric cancer prevalance is decreased significantly by the eradication of H. pylori infection. The Japanese Society for Helicobacter Research proposed that the cure of H. pylori infection should be presupposed to prevent gastric cancer from active gastritis universally developed in the infected subjects. Overall, the most important and dramatic revision is that all infected people are recommended to receive eradication therapy irrespective of the clinical outcomes in the Japanese population.